Effect of Dietary Agaricus bisporus and Auricularia auricula Crude Extract Suplementation on Carcass Quality of Broiler (Jurnal Ilmu dan Teknologi Hasil Ternak, 2020)
This research was conducted to examine Agaricus bisporus and Auricularia auricula crude extract using different solvents (water, ethanol, and methanol) on infrared spectroscopy absorbance during extraction and the impact on broiler carcass. Agaricus bisporus and Auricularia auricula crude extracts were scanned using fourier transform infrared (FT-IR) spectroscopy. Each mushroom crude extract was chosen and applied into broiler diets as feed additive at 0%, 0.4%, 0.8%, 1.2%, and compared zinc bacitracin inclusion. Variable measured were final live weight, carcass yield, breast meat yield, and abdominal fat yield of broiler. Two hundred and forty day-old chicks were randomly allocated into eight dietary treatments, each treatment was replicated three times with ten chicks for each pen. Diets and water were offered ad libitum. Methanolic extract showed monosaccharide absorption peak in fingerprint region at wavelength 890 cm-1, 930 cm-1, 1050 cm-1, 1150 cm-1 which indicates alpha and beta linkage than the others solvent. Even so, dietary inclusion of methanolic extracts of Agaricus bisporus and Auricularia auricula did not show any effect on final live weight and the yiled of carcass, breast meat and abdominal fat of broiler. In conclusion, methanolic extraction is effective to extract monosaccharides with Î±- and Î²- linkages from Agaricus bisporus and Auricularia auricula, while the dietary inclusion of methanolic extracts of both edible mushroom and zinc bacitracin has no effect on carcass quality of broilerin broiler diets did not show differences between treatments as well as zinc bacitracin group.